Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In the solution to the Newton-Pepys problem here, there's an identity applied on the third line to relate a binomial sum to the hypergeometric function 2F1. What is the general statement of the identity?

share|improve this question

1 Answer 1

up vote 2 down vote accepted

$$P_n = \sum _{x=n}^{6n} \binom{6n}{x}\left(\frac{1}{6}\right)^{x}\left(\frac{5}{6}\right)^{6n-x}\\ =\frac{5^{5n}}{6^{6n}}\binom{6n}{n}\sum_{x=n}^{6n}\frac{(5n)!n!}{x!(6n-x)!}5^{n-x}\\ =\frac{5^{5n}}{6^{6n}}\binom{6n}{n}\sum_{k=0}^{5n}\frac{(5n)!n!}{(k+n)!(5n-k)!}\frac{1}{5^k}\\ =\frac{5^{5n}}{6^{6n}}\binom{6n}{n}\sum_{k=0}^{5n}\frac{(5n-k+1)\cdots(5n)}{(n+1)\cdots(n+k)}\frac{1}{5^k}\\ =\frac{5^{5n}}{6^{6n}}\binom{6n}{n}\sum_{k=0}^{5n}\frac{(-5n)_k}{(n+1)_k}\left(-\frac{1}{5}\right)^k\frac{k!}{k!}\\ =\frac{5^{5n}}{6^{6n}}\binom{6n}{n}\sum_{k=0}^{5n}\frac{(-5n)_k(1)_k}{(n+1)_k}\left(-\frac{1}{5}\right)^k\frac{1}{k!}\\ =\frac{5^{5n}}{6^{6n}}\binom{6n}{n}{_2F_1}(1;-5n;n+1;-\frac{1}{5}).$$ I used this symbol as in Wikipedia's definition of hypergeometric series.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.